Efektivitas Kompres Hangat terhadap Intensitas Dismenorea pada Remaja Perempuan: Sebuah Studi Quasi-Eksperimental - Nopri Esmiralda; Erika Kusumawardani; Feranina Purba (Jurnal Sains dan Kesehatan, 2026)
Primary dysmenorrhea frequently disrupts the academic and daily activities of adolescent girls. This study evaluated the effectiveness of a 5-minute warm compress application in reducing menstrual pain intensity. A quasi-experimental study with a one-group pretest-posttest design was conducted on 42 female students of SMAN 28 Batam selected through purposive sampling. Participants applied a warm compress (40–45 °C) to the lower abdomen for 5 minutes. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. Data were analyzed using the Wilcoxon Signed-Rank test. Before the intervention, 42.9% of participants reported severe pain (NRS 7–10). After the 5-minute application, the severe pain category disappeared entirely (0%), with 57.1% of subjects shifting to the mild pain category (NRS 1–3). Statistical analysis showed a significant reduction in dysmenorrhea intensity (p < 0.001). A 5-minute warm compress application is a rapid and effective non-pharmacological intervention for relieving primary dysmenorrhea in adolescents. Its practicality makes this method a feasible self-care strategy to implement in school settings.